A Systematic Review of Various Physical Training Approaches in Athletics - I Gede Angga Andika; I Wayan Repiyasa; Muhammad Abi Sarwan (Jurnal Master Penjas & Olahraga, 2025)
This study aims to systematically analyze various physical training approaches in athletics. This research employed a systematic review. Article searches were conducted across five electronic databases: Google Scholar, PubMed, ScienceDirect, SPORTDiscus, and Directory of Open Access Journals (DOAJ), covering publications from 2013 to 2024. Inclusion criteria encompassed original research articles, systematic reviews, and meta-analyses discussing physical training in athletics. Data extraction and synthesis were performed thematically. From 47 articles meeting the inclusion criteria, six major training strategies were identified: (1) High-Intensity Interval Training (HIIT) and Sprint Interval Training (SIT) for improving VO2max and running economy; (2) Circuit training for cardiovascular endurance; (3) Plyometric training for explosive power development; (4) Sport-specific strength training for throwing events; (5) Periodization approaches for long-term training load management; and (6) Integration of wearable technology for real-time performance monitoring. The findings indicate that combined training approaches generally yield superior results compared to single-method interventions.